Analisis Faktor yang mempengaruhi Loyalitas Pelanggan (Studi kasus pada Leon Barbershop Brebes) - Faka Khaerul Birul Hasip; Syariefful Ikhwan; Robi Setiadi; Andi Yulianto (Universitas Nusa Nipa Maumere, 2023)
This study's main objective is to determine the effect of Public Relations, Brand Image, and Customer Value on Customer Loyalty at Leon's Barbershop which is located in Brebes District, Brebes Regency. The method used in this research is quantitative research. The research sample consisted of 222 respondents who were consumers of Leon's Barbershop, from a total population of 500 consumers. Data collection using a closed questionnaire was distributed to respondents through an online platform using the Google Form. Data collected from this questionnaire were analyzed using the Structural Equation Modeling technique to measure the relationship between variables such as Public Relations, Brand Image, and Customer Value on Customer Loyalty. The results showed that the Public Relations variable had a positive effect on customer loyalty with an estimated value of 0.266, a CR value of 2.137 (CR>1.96) and a probability of 0.033 (p<0.05). The brand image variable has no positive effect on customer loyalty because the estimated value is -0.082, the CR value is -0.549 (CR <1.96) and the probability value is 0.583 (p>0.05). The variable Customer value has a positive and significant effect on Customer Loyalty with an estimated value of 0.802, a CR value of 6.877 (CR>1.96) and a probability value of 0.000 (p<0.005). The variable that has the most influence on customer loyalty based on the estimated value is the Customer value variable.